Secondary school teachers’ perceptions of Catholic school management in selected schools of Lusaka District - Nyambe, Mwangala; Muzata, Kenneth Kapalu (S&Co Publishing, 2023)
This paper presents the findings of a study conducted to assess Catholic and non-Catholic teachers’ perceptions of Catholic schools’ management in five selected Catholic secondary schools in Lusaka District of Zambia. The objectives of the study were to examine the experiences of teachers teaching in Catholic schools; to assess the teachers’ perceptions of their school management in the Catholic schools, to establish aspects that influence negative perception of teaching in a Catholic school, and to investigate how religious restrictions affected the morale of teachers teaching in Catholic schools. The study used a qualitative approach and semi-structured interviews to generate data. Purposive sampling was used to select 25 participants that included five school head teachers; one in each school, ten Catholic teachers and ten non-Catholic teachers; two in each school that participated in the study. Data analysis was thematic. Among the key findings were that Catholic schools were managed via a strict school management model. Further findings revealed that key management positions were seen to be a preserve for Catholic teachers, management in the schools was perceived to be conservative and mass was made compulsory. Based on the findings, the study recommended the need to make the attendance of Mass, devotion, and other religious activities optional especially for non-Catholic teachers in order to respect religious choice and further adoption of flexible styles of management and minimum supervision of teachers. Positions in school management should be available for all teachers and learners and be based on merit first before religious faith.